Identification of 'Blue tears' and its relationship with water quality of coastal waters in Pingtan Island. (17th April 2023) - Zou, Yingbing; Chen, Junkun; Ma, Xiuling; Yang, Yuxiang; You, Jianyong; Chen, Qianhuo; Zheng, Yi; Xiang, Shengchang
This is the first example of research on the identification of 'Blue tears' and its effect on water quality. In view of the fascinating 'Blue tears' appearing in Pingtan Island from April to July in recent years, a survey on plankton and regular water quality was conducted in Pingtan related sea areas all throughout the year 2018. It showed that plankton increased sharply during the bloom of 'Blue tears' in May and June, and Noctiluca scintillans with bio-luminescence ability is one of the main dominant species, up to 50, 700 cells·L−1 in May. Phytoplankton availability largely determined the bloom of N. scintillans . Different from the reported work that Noctiluca scintillans may cause the sea water to deteriorate, the assimilative capacity of the coastal waters in Pingtan Island holds good. The growth and disappearing process of N. scintillans was also proposed.